Permanent exceptions to citizens: the stateless in South Asia. (2016) - Banerjee, Paula
The purport of this paper is to explain that citizenship and statelessness are part of the same grid. There are many people in South Asia who fall within that grid who will not be accepted as a citizen by competent authorities within a state and neither will they be called stateless by the international legal interpreters. Those in places like Geneva might say that these people should be called citizens by a particular state, and can be called a citizen if the citizenship laws of that state are improved, but the reality remains, the people in question are completely unable to access even the most elementary of the rights attributed to a citizen. This paper will map some of these indeterminate people in South Asia and discuss how national and international practices instead of helping them often leave them as permanent exceptions to citizenship.